Pengaruh Neglectful Parenting Style terhadap Emosi Negatif Anak Usia 5-6 Tahun dalam Pembelajaran - Nabilla Khanifa Salma; Rachma Hasibuan (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2023)
Neglectful parenting style is a parenting style that is low on two dimensions, namely response (warmth) and demands (control). This parenting style can lead to a child's lack of ability to manage emotions, thoughts, behavior (self-regulation), and child achievement in school. Negative emotions are unpleasant, disturbing, and generally expressed by dislike for something, such as anxiety, anger, guilt, and sadness. Negative impacts if children have difficulty managing emotions are speech disorders, confusion in expression, difficulty in socializing, and feeling restless, anxious, and uncomfortable. The purpose of this study was to determine the effect of neglectful parenting style on negative emotions of children aged 5-6 years in learning using a quantitative approach with a sample of 29 children aged 5-6 years or Group B children in TK Yamassa Surabaya. Data collection using questionnaires distributed via the internet to parents and teachers of children in Group B TK Yamassa Surabaya. The results of the study using a simple linear regression analysis showed neglectful parenting style affects the negative emotions of children aged 5-6 years in learning by 30.2% while the remaining 69.8% can be influenced by other factors such as the child's physical condition, environmental conditions, number of family members, socio-economic status of the family, and the child's place of residence.